Design Of Dual Band Antenna For WLAN Application - Abd. Aziz, Mohamad Zoinol Abidin; Othman, Mohd Azlishah; Ahmad, Badrul Hisham; Suaidi, Mohamad Kadim; Othman, Mohd Azlishah (Penerbit UTM Press, 2014)
This paper presents the antenna designed with radiating structure of 3.5 for dual band applications.This antenna is designed and simulated by using CST Studio Suite software at 2.4 GHz and 5.2 GHz based on standard IEEE 802.11a (5.15 GHz-5.35 GHz) and IEEE 802.11b (2.4 GHz-2.48 GHz) frequency bands.The radiating structure 5 and 3 are designed to radiated at frequency 2.4 GHz and 5.2 GHz respectively.Then,both structures are combined to achieve dual band resonant frequencies. The techniques that have been used to achieve dual band resonant are by designing the 3.5 shaped by using planar and coplanar waveguide (CPW) structures.There are three designs of dual band antenna which are Design A,Design B and Design C.The optimum return loss for 2.4 GHz and 5.2 GHz frequency response are -16.44 dB and - 18.78 dB respectively achieved by Design C.The changes on the position of radiating structure 3 will effects the frequency response,return loss and gain of the antenna.